Can you detect early dementia from an email? A proof of principle study of daily computer use to detect cognitive and functional decline. (9th February 2018) - Stringer, G.; Couth, S.; Brown, L.J.E.; Montaldi, D.; Gledson, A.; Mellor, J.; Sutcliffe, A.; Sawyer, P.; Keane, J.; Bull, C.; Zeng, X.; Rayson, P.; et al.
Abstract : Objective: To determine whether multiple computer use behaviours can distinguish between cognitively healthy older adults and those in the early stages of cognitive decline, and to investigate whether these behaviours are associated with cognitive and functional ability. Methods: Older adults with cognitive impairment ( n  = 20) and healthy controls ( n  = 24) completed assessments of cognitive and functional abilities and a series of semi‐directed computer tasks. Computer use behaviours were captured passively using bespoke software. Results: The profile of computer use behaviours was significantly different in cognitively impaired compared with cognitively healthy control participants including more frequent pauses, slower typing, and a higher proportion of mouse clicks. These behaviours were significantly associated with performance on cognitive and functional assessments, in particular, those related to memory. Conclusion: Unobtrusively capturing computer use behaviours offers the potential for early detection of neurodegeneration in non‐clinical settings, which could enable timely interventions to ultimately improve long‐term outcomes.